2015
DOI: 10.1515/cttr-2015-0022
|View full text |Cite
|
Sign up to set email alerts
|

Prediction Model for Cigarette Yields Derived from Data Obtained under Two Different Machine Smoking Regimes

Abstract: Summary“Tar”, nicotine and carbon monoxide (TNCO) cigarette yields determined under different smoking regimes, with and without ventilation blocking, are linearly related to the difference Δt between the smouldering time (cigarette combustion with no puffing) and the smoking time (cigarette combustion with puffing). Δt forms then the basis of yield predictions. The smoulder rate determination used in the calculation of Δt can be difficult for low ignition propensity cigarettes which present some tendency for s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…The second estimation was based on the linear relationship between the smoke nicotine and the active smoking time (smouldering time minus cigarette smoking time) described previously by this group of authors (27,28). We showed that MS-Nic and MS-"tar" yields among other smoke constituents are linearly related to the difference between the smouldering time (cigarette combustion with no puffing) and the machine smoking time, MST (cigarette combustion with puffing).…”
Section: Estimation Of Human Smoking Nicotine Yields Using Smoking Timementioning
confidence: 77%
“…The second estimation was based on the linear relationship between the smoke nicotine and the active smoking time (smouldering time minus cigarette smoking time) described previously by this group of authors (27,28). We showed that MS-Nic and MS-"tar" yields among other smoke constituents are linearly related to the difference between the smouldering time (cigarette combustion with no puffing) and the machine smoking time, MST (cigarette combustion with puffing).…”
Section: Estimation Of Human Smoking Nicotine Yields Using Smoking Timementioning
confidence: 77%